Altering the Mitochondrial Fatty Acid Synthesis (mtFASII) Pathway Modulates Cellular Metabolic States and Bioactive Lipid Profiles as Revealed by Metabolomic Profiling - Clay, Hayley B.; Parl, Angelika K.; Mitchell, Sabrina L.; Singh, Larry; Bell, Lauren N.; Murdock, Deborah G. (PLOS ONE, 2016)
Despite the presence of a cytosolic fatty acid synthesis pathway, mitochondria have retained their own means of creating fatty acids via the mitochondrial fatty acid synthesis (mtFASII) pathway. The reason for its conservation has not yet been elucidated. Therefore, to better understand the role of mtFASII in the cell, we used thin layer chromatography to characterize the contribution of the mtFASII pathway to the fatty acid composition of selected mitochondrial lipids. Next, we performed metabolomic analysis on HeLa cells in which the mtFASII pathway was either hypofunctional (through knockdown of mitochondrial acyl carrier protein, ACP) or hyperfunctional (through overexpression of mitochondrial enoyl-CoA reductase, MECR). Our results indicate that the mtFASII pathway contributes little to the fatty acid composition of mitochondrial lipid species examined. Additionally, loss of mtFASII function results in changes in biochemical pathways suggesting alterations in glucose utilization and redox state. Interestingly, levels of bioactive lipids, including lysophospholipids and sphingolipids, directly correlate with mtFASII function, indicating that mtFASII may be involved in the regulation of bioactive lipid levels. Regulation of bioactive lipid levels by mtFASII implicates the pathway as a mediator of intracellular signaling.